Unveiling the complexity of vaccine hesitancy: A narrative review focusing on dengue vaccination - Rachata Charoenwisedsil; Saranath Lawpoolsri; Pinyo Rattanaumpawan; Daniel Y. T. Goh; Gerard T. Flaherty; Thundon Ngamprasertchai (Human Vaccines & Immunotherapeutics)
Dengue vaccines face significant challenges, including safety concerns, which contribute to vaccine hesitancy. Addressing this complex issue requires targeted strategies to overcome existing barriers. Through an extensive review of current evidence, we identified key factors contributing to vaccine hesitancy and explored strategies to enhance global vaccine uptake. Four conceptual models and five assessment tools were identified to understand and measure vaccine hesitancy. Among the factors, “confidence” emerged as the most influential, followed by “complacency.” Vaccine acceptance rates varied widely, ranging from 53% to 95%, depending on the region and population. Key determinants included population characteristics, concerns about efficacy and safety, among others. A comprehensive understanding of these factors is essential to improve vaccine acceptance, support dengue prevention efforts, and ensure public health success.